Pengaruh Latihan Static Stretching dan Latihan Reciprocal Inhibition Untuk Peningkatan Fleksibilitas Otot Hamstring Pada Pemain Futsal - Abdhany, Fian Akbar; , Dwi Rosella K S, S.Fis, M.fis (2016)
Background: flexibility is one of the main components in futsal game where futsal is known as the dynamic sport therefore we need a good flexibility muscle. The hamstring muscle is one of the muscle that has a role while we run, driblle and kick the ball. Therefore we will need a good hamstring muscle flexibility to make a good perform and avoid injury hamsting muscle. Objectives: to determine the effect of static strecthing exercise and reciprocal inhibition exercise to improve flexibility of the hamstring muscle in futsal players. Research methods: this research methods use quari experimental methods with use pretest and post - two groups design. This research takes 18 people as the sample. This research is devided two groups which each group consist of nine people. The first group will given exercise with stand static stretching by holding for 30 seconds repeated for three times. It is done three times in a week for four week. The second group will given exercise ireciprocal inhibition by holding for 10 seconds repeated for three times. It is done three times in a week for four week. Measuring instrument is taken using active knee extension. This instrument uses a goniometer that measured before treatment (0-session) and after treatment 12-session) on each subject. Result: the effect test in group I with static stretching exercise right and left gets p values=0.007 (p>0.005) while in group II with reciprocal inhibition exercise of the right and left gets p lues=0.007 (p>0.005). It states tes data differently after get treatment between group I and group II with right p=0.115 and left p=0.108. Mean right side of the group I=10.61> group II=8.28. While mean left side of the group I=10.05>group II=8.17. Conclution:static stretching and reciprocal inhibition exercise are equally influential in improving the flexibility of the hamstring muscle in futsal players. However, static stretching exercise is more influential than the reciprocal inhibition exercise.